O erotismo profano de Hilda Hilst e a erótica animalesca de Olga Savary: veredas na desconstrução do imaginário feminino - Santana, Patrícia Maria dos Santos (2011)
This work aims at analyzing some erotic and intimate poems written by Olga Savary (May 21st , 1933, Belém, Pará) and Hilda Hilst (April 21st, 1930, Jaú, São Paulo - February 4 th , 2004, Campinas, São Paulo) in their respective books related to the erotic theme called Magma and Do Desejo. For the mentioned works being the first ones about eroticism in Brazil, it is extremely interesting to have a comparative study about both books. The theme can be the same but the way each poetess faces eroticism is completely different: Hilda Hilst discuss her own sexuality, her erotic side facing God and the whole world, while Olga Savary puts her erotic side in her animal instinct as if she were a wild animal looking for sex. Through these tricks of the art of making poetry, both authors try to deconstruct the way society sees women in general, making use of many resources to face the social stereotypes.